Kabale University Convocation Constitution - Kabale University (Kabale University, 2022)
The Convocation Premises shall be at Kabale University, Kikungiri, Kabale Municipality. The Executive Committee shall carry out Convocation activities either in office space provided by the University or in premises built by Convocation on space allocated by the University. At an Annual General Meeting, the Convocation may decide to open branch office(s) in area(s) deemed deserving of such office(s).